THE RELATIONSHIP PROVIDES EXCLUSIVE BREASTFEEDING WITH THE NUTRITIONAL STATUS OF INFANTS AGED 0 – 6 MONTHS AT THE COMMUNITY HEALTH CENTER MENGANTI VILLAGE, GLAGAH DISTRICT, LAMONGAN REGENCY - Mei Tyas, Anestasia Pangestu; Saikudin, Guntoro (Universitas Airlangga, 2020)
Introduction: Nutritional needs are a very important requirement for a baby's growth and development. Most of the nutrients needed for babies aged 0-6 months are determined by the quantity and quality of mother's milk because exclusive breastfeeding has a balanced composition and is ideal for babies. The problem of malnutrition is considered by the community as a matter of course so often babies who experience malnutrition are not taken to the community health center or hospital. from the results of a preliminary study in Menganti Village, Glagah Subdistrict, Lamongan Regency, out of 10 babies aged 0-6 months, 10% of infants with poor nutritional status were found. The purpose of this study was to analyze the relationship between exclusive breastfeeding and the nutritional status of infants aged 0-6 months. Methods: The design of this study is a correlation study with a cross sectional approach, with a mother population of 26 respondents, a sample of 25 respondents. Sampling using simple random sampling technique, data taken using questionnaire sheets and observation sheets, then analyzed by spearman test with a significance level of 5 0.05. Results: The results showed that (40%) mothers gave exclusive breastfeeding and (72%) babies had good nutritional status. The statistical test results obtained rs = 0.345 and p = 0.092, where p> 0.05.. Conclusion: The conclusion in this study is that there is no relationship between exclusive breastfeeding and infant nutritional status. The implications of this study require the role of health workers to provide health education to mothers about breastfeeding that is appropriate for infants